Enzymatic treatment of methyl orange dye in synthetic wastewater by plant-based peroxidase enzymes - Chiong, T.; Lau, John; Lek, Z.; Koh, B.; Danquah, M. (Elsevuer BV, 2016)
The search for effective and sustainable methods to degrade and remove recalcitrant dyes from textile effluents is a major research endeavor, owing to the escalating environmental and health concerns arising from the discharge of coloured effluents into water bodies. Plant-based peroxidases represent a reliable bio-resource for sustainable treatment of coloured effluents with the capacity to offer a continuous process for high throughput operation. The present study investigates the potential use of soybean peroxidase and Luffa acutangula (luffa) peroxidase, extracted from bio-wastes of soybean hulls and luffa skin peels respectively, for enzymatic degradation of azo dye methyl orange from liquid effluents. The enzymatic dye removal process was studied based on the consistent enzymatic activities of crude soybean peroxidase and luffa peroxidase extracts, which were 0.373 U mL-1 and 0.355 U mL-1 respectively. The effects of several process parameters including reaction time, pH, temperature, enzyme dosage, initial dye concentration and hydrogen peroxide concentration were investigated to optimise the performance of the enzymatic treatment process. Soybean peroxidase demonstrated a maximum dye decolourisation efficiency of 81.4% under the conditions of 1 h incubation at 30 °C using 2 mM of hydrogen peroxide, 0.5 mL crude soybean peroxidase and 30 mg L-1 methyl orange at pH 5.0. Also, luffa peroxidase yielded a maximum decolourisation efficiency of 75.3% under the conditions of 40 min at 40 °C using 2 mM hydrogen peroxide, 1.5 mL crude luffa peroxidase and 10 mg L-1 methyl orange at pH 3.0.